KONDISI KINI DAN PELUANG MENGEMBANGKAN DUKU - Kartini M. Deroes; Andi Wijaya (Publikasi Penelitian Terapan dan Kebijakan, 2020)
Duku germplasm source is South East Asia. Duku trees are mostly cultivated in Malaysia, Thailand, and Indonesia. Duku have been known by Indonesian community more than hundred years ago. Duku trees grown almost in all over provinces. There are an indication of increasing duku consumption among the society. In contrary, duku trees are still undercultivated. Mostly, duku trees are traditionally planted and existing trees are relatively old. Duku growers hardly apply good agricultural practices on their duku trees. Sometimes, harvesting time is shifted due to climate change, ie rainy season. In marketing duku fruits, growers have low bargaining position. In order to develop duku production and good marketing system, aiming to raise growers income, comprehensive-integrated long term research and development program should be done. The ultimate goal of the program should be included, production of high quality duku seedlings, development of cultivation methods (Good Agricultural Practices), development of harvest/postharvest technology (Good Handling Practices), and development of duku agribusinesssystem (SCM).